Relationship of severity of hyponatremia and adverse outcomes in children visiting the emergency department - Ryoo, Jisu; Choi, Arum; Cho, Hyunchul; Bae, Woori (Frontiers in Pediatrics, 2024)
Mild hyponatremia is often found in patients visiting pediatric emergency departments (PEDs), but there are few large-scale studies on its association with adverse outcomes, including mortality. We conducted this study to identify the association of mild hyponatremia with adverse outcome. This retrospective observational study included children under 18 years of age visiting the PED at a tertiary hospital. We used electronic medical record data from January 1, 2009 to December 31, 2020. Clinical outcomes, including ward admission, vasopressor administration, pediatric intensive care unit (PICU) admission, and mortality, were assessed for the total of 44,147 patients. Among these, 1,639 (3.7%) were in the hyponatremia group, with 1,521 (3.4%) exhibiting mild hyponatremia. Mild hyponatremia was more prevalent in younger patients, particularly in the 1–3 years age group, and less common in females. Patients with mild hyponatremia had a significantly prolonged median length of stay in the PED compared to normonatremic patients (5.8 h vs. 4.4 h, p < 0.001). Moreover, they showed significantly higher rates of ward admission (51.1% vs. 35.6%, p < 0.001), vasopressor administration (1.1% vs. 0.6%, p = 0.014), PICU admission (2.4% vs. 1.0%, p < 0.001), and mortality (1.5% vs. 0.3%, p < 0.001). Compared with the normonatremia group, the odds ratios (95% CI) for ward admission, vasopressor administration, PICU admission, and mortality in the mild hyponatremia group were 1.90 (1.71–2.10), 1.91 (1.17–3.13), 2.62 (1.86–3.68), and 5.56 (3.51–8.80), respectively. Furthermore, our findings demonstrate a notable upward trend in adverse outcomes, including vasopressor administration, PICU admission, and mortality, from mild hyponatremia to severe hyponatremia. In conclusion, we found that adverse outcomes increase with the severity of hyponatremia in children presenting to the PED, highlighting the importance of immediate intervention alongside the identification of the underlying cause.